2008
DOI: 10.1097/shk.0b013e318150762b
|View full text |Cite
|
Sign up to set email alerts
|

Il-6 Modulates Sepsis-Induced Decreases in Transcription of Hepatic Organic Anion and Bile Acid Transporters

Abstract: Sepsis, a lethal inflammatory syndrome, is characterized by organ system dysfunction. In the liver, we have observed decreased expression of genes encoding proteins modulating key processes. These include organic anion and bile acid transport. We hypothesized that the inflammatory mediator IL-6 modulates altered expression of several key hepatic genes in sepsis via induction of the intracellular transcription factor signal transducer and activator of transcription (Stat) 3. Sepsis was induced in IL-6 +/+ and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
(67 reference statements)
1
34
0
1
Order By: Relevance
“…During live infection we observed a significant decrease in the mRNA expression of Abcc2 in C57BL/6J mice. Other inflammatory conditions have been reported to result in similar downregulation (Andrejko et al, 2008;Sharma et al, 2008;Cherrington et al, 2013). Multiple studies have indicated a role for IL-6 in the downregulation of Abcc2 (Siewert et al, 2004;Andrejko et al, 2008).…”
Section: Drug Transporter Expression During C Rodentium Infection 599mentioning
confidence: 96%
See 2 more Smart Citations
“…During live infection we observed a significant decrease in the mRNA expression of Abcc2 in C57BL/6J mice. Other inflammatory conditions have been reported to result in similar downregulation (Andrejko et al, 2008;Sharma et al, 2008;Cherrington et al, 2013). Multiple studies have indicated a role for IL-6 in the downregulation of Abcc2 (Siewert et al, 2004;Andrejko et al, 2008).…”
Section: Drug Transporter Expression During C Rodentium Infection 599mentioning
confidence: 96%
“…Other inflammatory conditions have been reported to result in similar downregulation (Andrejko et al, 2008;Sharma et al, 2008;Cherrington et al, 2013). Multiple studies have indicated a role for IL-6 in the downregulation of Abcc2 (Siewert et al, 2004;Andrejko et al, 2008). In the current study, the decrease in Abcc2 expression in IL-6-null mice failed to reach statistical significance, but the decrease did not appear to be meaningfully different from that seen in their WT controls.…”
Section: Drug Transporter Expression During C Rodentium Infection 599mentioning
confidence: 96%
See 1 more Smart Citation
“…Intrahepatic bile acid transport is among many of BEC important functions (26). We next examined the expression of hepatic bile acid transport genes, which are known target genes for HNF: ntcp (the Na ϩ -dependent taurocholate cotransport peptide for bile acid import, also known as slc10a1) is transcriptionally regulated by HNF1a (13) and HNF4a (13,16); mrp2 (the multidrug resistanceassociated protein for xeno-and endobiotics bile acid export, also known as abcc2) by HNF1a and HNF4a (20,32), and possibly by Foxa2 (7); and oatp1 (the organic anion transporter for basolateral bile acid uptake, also known as slc21a1) by HNF1a (4,27) and HNF4a (11,16). Since the above data showed that SV40LG and SV40SM cells have differential expression of Foxa2, HNF1a, and HNF4a transcription factors, we next sought to characterize the baseline expression of HNF6, Foxa2, HNF1a, and HNF4a target genes.…”
Section: Ajp-gastrointest Liver Physiolmentioning
confidence: 99%
“…In endotoxemic and septic animal studies and in critically ill humans, gene expression and protein levels of the basolateral uptake pump NTCP are markedly downregulated, likely due to suppression of essential transcription factors by pro-inflammatory cytokines [44][45][46]. The OATP uptake transporters are also downregulated by inflammation-induced mechanisms [45][46][47].…”
Section: Bile Acid Transport During Critical Illnessmentioning
confidence: 93%